Application and Validation of Simple Isocratic HPLC-UV-DAD Method with Dual Wavelength Detection for Ivabradine Determination and Its Application in the Study of Stress Degradation - Joanna Nowakowska; Piotr Pikul; Marcin Marszałł; Krzesimir Ciura (Journal of Chemistry)
Ivabradine is a modern drug that selectively lowers the heart rate, improves cardiac energy balance, and reduces heart’s demands for oxygen and energy. Due to the chemical nature of ivabradine, which absorbs light at 207 nm and 286 nm, its detection was performed at two wavelengths. A Knauer C8 column was used to develop the RP-HPLC method for determination of ivabradine. The proposed method was linear from 5 to 100 µg/ml (r>0.999) for both wavelengths and limits of detection (LOD) and limits of quantification (LOQ) were 0.33 and 1.09 µg/ml for 207 nm and 1.19 and 3.97 µg/ml for 286 nm, respectively. After validation, the investigated method was applied to a stress degradation study. Numerous degradation products were formed from ivabradine solutions through alkaline and acid hydrolysis, oxidation, and photolysis. The largest numbers of degradation products were found in the sample exposed to 24 h radiation and alkaline hydrolysis (eight and six products, resp.). Finally, the simple method using HPLC-UV-DAD was developed and validated. Its usefulness for the monitoring of possible degradation products was demonstrated.